2017
DOI: 10.3389/fcimb.2017.00217
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Phenotypic Changes Define Neutrophil Priming

Abstract: Exposure to pro-inflammatory cytokines, chemokines, mitochondrial contents, and bacterial and viral products induces neutrophils to transition from a basal state into a primed one, which is currently defined as an enhanced response to activating stimuli. Although, typically associated with enhanced generation of reactive oxygen species (ROS) by the NADPH oxidase, primed neutrophils show enhanced responsiveness of exocytosis, NET formation, and chemotaxis. Phenotypic changes associated with priming also include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(204 citation statements)
references
References 186 publications
(148 reference statements)
6
192
0
6
Order By: Relevance
“…This result suggests that F. alocis secreted products are not involved in the low ROS levels generated in F. alocis challenged neutrophils. During an inflammatory setting in vivo , quiescent neutrophils can change into a pre-activated phenotype or primed cell due to exposure to inflammatory cytokines such as TNF-α, interleukin (IL)-1β and IL-17 (Kruger, Saffarzadeh, Weber, Rieber, Radsak, von Bernuth, … Hartl, 2015; Miralda, Uriarte, & McLeish, 2017). Primed neutrophils have a more robust response when encountering a second stimulus, but a priming agent, such as TNF-α, by itself does not result in generation of oxidants (Condliffe, Kitchen, & Chilvers, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that F. alocis secreted products are not involved in the low ROS levels generated in F. alocis challenged neutrophils. During an inflammatory setting in vivo , quiescent neutrophils can change into a pre-activated phenotype or primed cell due to exposure to inflammatory cytokines such as TNF-α, interleukin (IL)-1β and IL-17 (Kruger, Saffarzadeh, Weber, Rieber, Radsak, von Bernuth, … Hartl, 2015; Miralda, Uriarte, & McLeish, 2017). Primed neutrophils have a more robust response when encountering a second stimulus, but a priming agent, such as TNF-α, by itself does not result in generation of oxidants (Condliffe, Kitchen, & Chilvers, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we extended these findings to show that 10% serum opsonized F. alocis induced secretory vesicles, gelatinase and specific granule exocytosis, but not azurophil granules; a process that was not dependent on bacterial viability except in the case of the secretory vesicles. Degranulation has been shown to be a critical step in the priming and activation of neutrophils (Miralda, Uriarte, & McLeish, 2017; Uriarte, Rane, Luerman, Barati, Ward, Nauseef, & McLeish, 2011). Previous studies have shown that F. alocis induced the release of pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 by epithelial cells which could result in priming and/or activation of human neutrophils (Moffatt, Whitmore, Griffen, Leys, & Lamont, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils require a first stimulus to prepare them for the release of specific granule contents upon exposure to a second stimulus. This sequential “two‐hit” model for enhanced neutrophil responses is commonly referred to as “priming.” Transmigration in vivo induces extracellular release of 22% of specific granules . Specific granules fuse with nascent phagosomes as part of their general translocation to the plasma membrane .…”
Section: Granulopoiesis and Granule Contentsmentioning
confidence: 99%
“…Generation of ROS by the NADPH oxidase and release of antimicrobial proteins during granule mobilization provide synergistic antimicrobial activity . Both processes are enhanced, or primed, upon neutrophil exposure to chemokines, cytokines, or microbial and cell products . Recent studies indicate that priming of granule mobilization and oxidase activity are linked.…”
Section: Role Of Exocytosis In Neutrophil Functionmentioning
confidence: 99%
“…Neutrophils derive from promyeloid progenitors and leave the bone marrow as fully differentiated cells to enter the blood circulation . Unlike other myeloid and lymphoid immune cells, neutrophils do not further differentiate outside the bone marrow but their bactericidal potency can be enhanced by cytokines, chemokines, or microbial products . During infection, the circulating cells are recruited from the blood stream to inflamed tissue following chemotactic gradients, a multistep process that is finely regulated …”
Section: Introductionmentioning
confidence: 99%